Empirical Study of Female Workers of Informal Sectors in Delhi and Their Work Profile (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
There has been increasing informalization of  activities through well-established linkages  between formal and informal activities and  organized and unorganized sector. For faster  growth and inclusiveness there has to be emphasis  on the informal sector and its development  specially women through addressing needs of  skill, technology, dignity of workforce, social  security, infrastructure and marketing. A clear  policy is imperative for non-agricultural jobs  engaging female workers with emphasis on  quality of jobs. This paper describes the profile  like nature of work, industry of work, working  conditions, hours of work, work related benefits.  Secondly, it also estimates the persistence of  Informality in female workers of the informal  sector. The study has adopted a descriptive  method of research and investigational approach  with sample size of 359 respondents. The paper  brings forward that in the informal sector of  Delhi, self-employment among female workers  belonging to adolescence and as adult women  workers remains the main choice of the work As  far as working hours are concerned the younger  females work longer durations as compared to  women more than 19 years as they are engaged  in taking care of children, sick adults, domestic  chores, etc. Despite working at home, they seek  gainful engagement in the informal sectors as  per the time they could devote to contributing  to the family economically. Poverty, inadequate  family income, meeting demands of bad habits  of male members, tradition for women to work  is the major persisting reasons for their working  in the informal sector.
Keywords: Women workers; informal sector; work profile